Interdisciplinary training program for pediatric cardiorespiratory arrest using rapid cycle deliberate practice: a descriptive cross-sectional study - Pereira, Renata; Silva, Edina Mariko Koga da (São Paulo Medical Journal, 2025)
BACKGROUND: cardiorespiratory arrest (CRA) is a severe public health concern, and clinical simulation has proven to be a beneficial educational strategy for training on this topic. OBJECTIVE: To describe the implementation of a program for pediatric cardiac arrest care using rapid-cycle deliberate practice (RCDP), the quality of the technique employed, and participants’ opinions on the methodology. DESIGN AND SETTING: This descriptive cross-sectional study of pre- and post-performance training in cardiopulmonary resuscitation (CPR) techniques and reaction evaluation was conducted in a hospital in São Paulo. METHODS: Multidisciplinary groups performed pediatric resuscitation in a simulated scenario with RCDP mediated by a facilitator. The study sample included professionals working in patient care. During the simulation, the participants were evaluated for their compliance with the CRA care algorithm. Further, their execution of chest compressions was assessed pre- and post-intervention. RESULTS: In total, 302 professionals were trained in this study. The overall quality of CPR measured pre-intervention was inadequate, and only 26% had adequate technique proficiency, whereas it was 91% (P < 0.01) post-intervention. Of the participants, 95.7% responded to the final evaluation and provided positive comments on the method and their satisfaction with the novel simulation. Of these, 88% considered that repetition of the technique used was more effective than traditional simulation. CONCLUSIONS: The RCDP is effective for training multidisciplinary teams in pediatric CPR, with an emphasis on the quality of chest compressions. However, further studies are necessary to explore whether this trend translates to differential performances in practical settings.